Mastering vrealize operations manager : analyze and optimize your it environment by gaining a practical understanding of vrealize operations 6.6 /: analyze and optimize your it environment by gaining a practical understanding of vrealize operations 6.6. (2018) - Kaloferov, Spas; Slater, Chris; Carnie, Alasdair; Norris, Scott, 1982 or 1983-
No abstract available